'Ahhh it was like paradise, but inside': children's experiences and perceptions of a free physical activity program. Issue 3 (4th May 2023) - Ostermeier, Emma; Reilly, Kristen; Nelson Ferguson, Kendra; Coen, Stephanie E.; Gilliland, Jason
ABSTRACT: As most Canadian children are not attaining the recommended 60 minutes of daily physical activity, it is imperative that affordable and accessible programs are implemented to help children become more physically active. Specifically, community-based programs that are free and easy to access have shown to be advantageous for promoting beneficial health behaviours at a population level. The Grade 5 ACT-i-Pass (G5AP) is a community-based physical activity program in the mid-sized Canadian city of London, Ontario that offers free programming to all grade 5 children (ages 9–11 years) at various recreational facilities across the city. The data from 28 focus groups with past G5AP participants (n = 101) were analysed to understand the influence of the program on children's perceived physical activity levels, and to investigate the enablers and/or barriers that children believe influenced their participation in, or access to, G5AP programming. Five distinct themes were identified during the analysis, including two themes describing participants' perceived changes to their physical activity levels (i.e. additional physical activity opportunities, and well-being and self-efficacy), and three themes explaining enablers and/or barriers to G5AP programming (i.e. program structure and implementation, spatial accessibility of programming, and social supports and constraints). The findings from the focus groups were used to generate recommendations for current and future community-based physical activity programs as a means to improve the health and well-being of children.